Guest

( *) If x sec theta + y tan theta = a, x tan theta + y sec theta = b then a square – b square =

( *)
If x sec theta + y tan theta = a, x tan theta + y sec theta = b then a square – b square =

Grade:11

1 Answers

Yash Baheti IIT Roorkee
askIITians Faculty 97 Points
8 years ago
Hi,

Follow the following steps :

Just pur the values of a^2 and b^2 and expand.
You will see that some terms will cancel out and some can be combined via using the identity :
SEC^2 – TAN^2 = 1.

Your final answer will be x^2+y^2

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free